EXCEEDING THE BUDGET DEFICIT AND ADOPTING MEASURES FOR DIFFERENT RECIPIENTS WITHOUT TAKING INTO ACCOUNT THE EFFECTS THEY MAY GENERATE OVER TIME - Beatrice NICULAE (Challenges of the Knowledge Society)
With this article, we propose to analyse the way in which the implementation of the measures to reduce the budget deficit was decided in Romania. Thus, we are particularly concerned with the provisions of Law no. 296/2023 on some fiscal-budgetary measures to ensure Romania's long-term financial sustainability, a normative act that at first glance positions itself correctly towards its recipients, but on closer reading, has the potential to generate negative effects, at least with regard to economic operators with state capital that can be considered profitable. We will analyse, for example, the bans imposed, in relation to their generality, without taking into account the long-term effects, and here we have in mind the fluctuation and ageing of staff, but also the lack of any means of encouraging production. However, as long as employees are aware that the company has made a profit, if it is not reflected at the salary level (bonuses, meal vouchers), even though this has happened in previous years, they will become dissatisfied, with the direct consequence being a drop in productivity and, implicitly, in the current year's profit. That is why, having analysed the above-mentioned normative act, we have come to the conclusion that it needs to be amended, at least with regard to some measures, especially those related to the granting of bonuses at salary level. We admit that measures to reduce the budget deficit are necessary, but this cannot be achieved by imposing bans that apply to different categories of recipients, without taking into account possible, well-justified exceptions. If the legislation does not change, surely memoranda will be formulated regarding the exemption of the economic operators concerned from the total/partial application, as the case may be, of the provisions of Law no. 296/2023.